Divergent Innate and Epithelial Functions of the RNA-Binding Protein HuR in Intestinal Inflammation - Christodoulou-Vafeiadou, Eleni; Ioakeimidis, Fotis; Andreadou, Margarita; Giagkas, Giorgos; Stamatakis, George; Reczko, Martin; Samiotaki, Martina; Papanastasiou, Anastasios D.; Karakasiliotis, Ioannis; Kontoyiannis, Dimitris L. (Frontiers in Immunology, 2018)
HuR is an abundant RNA-binding protein acting as a post-transcriptional regulator of many RNAs including mRNAs encoding inflammatory mediators, cytokines, death signalers and cell cycle regulators. In the context of intestinal pathologies, elevated HuR is considered to enhance the stability and the translation of pro-tumorigenic mRNAs providing the rationale for its pharmacological targeting. However, HuR also possesses specific regulatory functions for innate immunity and cytokine mRNA control which can oppose intestinal inflammation and tumor promotion. Here, we aim to identify contexts of intestinal inflammation where the innate immune and the epithelial functions of HuR converge or diverge. To address this, we use a disease-oriented phenotypic approach using mice lacking HuR either in intestinal epithelia or myeloid-derived immune compartments. These mice were compared for their responses to (a) Chemically induced Colitis; (b) Colitis- associated Cancer (CAC); (c) T-cell mediated enterotoxicity; (d) Citrobacter rodentium-induced colitis; and (e) TNF-driven inflammatory bowel disease. Convergent functions of epithelial and myeloid HuR included their requirement for suppressing inflammation in chemically induced colitis and their redundancies in chronic TNF-driven IBD and microbiota control. In the other contexts however, their functions diversified. Epithelial HuR was required to protect the epithelial barrier from acute inflammatory or infectious degeneration but also to promote tumor growth. In contrast, myeloid HuR was required to suppress the beneficial inflammation for pathogen clearance and tumor suppression. This cellular dichotomy in HuR's functions was validated further in mice engineered to express ubiquitously higher levels of HuR which displayed diminished pathologic and beneficial inflammatory responses, resistance to epithelial damage yet a heightened susceptibility to CAC. Our study demonstrates that epithelial and myeloid HuR affect different cellular dynamics in the intestine that need to be carefully considered for its pharmacological exploitation and points toward potential windows for harnessing HuR functions in intestinal inflammation.